Діалоги на відстані (приватне листування Юрія Шевельова) - Денисенко, О. (Літературознавчі обрії. Праці молодих учених, 2010)
A part of an epistolary heritage in which submitted the information of estimating character which concerns to the literature and language and personal circumstances of Yury Shevelov’s life is analyzed in this article. The central aim of this work is to present an analysis of letters of Yury Shevelov’s to Olexa Gorbach, Oxana Solovey, Oxana Zabuzhko. Introduction in a scientific turn of the described materials will promote a deepening of the further researches.